2022
DOI: 10.1155/2022/1507881
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Limitations of Sentinel Lymph Node Biopsy after Neoadjuvant Chemotherapy in Breast Cancer Patients with Positive Nodes

Abstract: Background. Axillary surgical management in patients with node-positive breast cancer at the time of diagnosis converted to negative nodes through neoadjuvant chemotherapy (NAC) remains unclear. Removal of more than two sentinel nodes (SLNs) in these patients may decrease the false negative rate (FNR) of sentinel lymph node biopsies (SLNBs). We aim to analyse the detection rate (DR) and the FNR of SLNB assessment according to the number of SLNs removed. Methods. A retrospective study was performed from October… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In their study, Aragon-Sanchez et al [ 42 ] retrospectively analysed the accuracy of SLNB after neoadjuvant chemotherapy in 85 patients who were initially cN1 and converted to cN0 following treatment. Their research revealed that SLNB demonstrated an adequate IR of 92.9%, but with a relatively high FNR of 19.1%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study, Aragon-Sanchez et al [ 42 ] retrospectively analysed the accuracy of SLNB after neoadjuvant chemotherapy in 85 patients who were initially cN1 and converted to cN0 following treatment. Their research revealed that SLNB demonstrated an adequate IR of 92.9%, but with a relatively high FNR of 19.1%.…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion criteria were met by 20 papers, which were finally included in this qualitative review. Most researcher groups (n = 11) used a combination of 99m Tc-labelled radioisotopes and BD for their SLN mapping [ 24 , 28 , 29 , 30 , 31 , 32 , 37 , 38 , 39 , 40 , 41 ], while nine studies performed SLN identification through radioisotopic mapping alone [ 9 , 18 , 26 , 33 , 34 , 35 , 36 , 42 ]. In all papers, SLNB was followed by ALND to ensure the accurate assessment of the axilla.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 However, only 32.0-56.4% of patients staged by SLNB have three or more SNs identified. 3 , 6 , 9 , 10 The development of a less-invasive staging technique for lymph node-positive patients receiving NACT seems imperative, considering that 31.4-63.0% of patients have axillary complete pathologic response (ax-pCR). 3 , 5 , 11 13 These patients do not benefit from axillary lymph node dissection (ALND) but are nevertheless imposed to the possible morbidity associated with the procedure.…”
mentioning
confidence: 99%